27.6k views
3 votes
Asking this question again,help me please​

Asking this question again,help me please​-example-1
User EHB
by
6.0k points

1 Answer

7 votes


r(1) = (2 \: .1 \: . (2)/(3) )


r(0) = (0 \: .0 \: .0)


\gamma r =( 2 \: .1 \: . (2)/(3) )


l = \sqrt{2 {}^(2) + 1 {}^(2) + (4)/(9) }


l = \sqrt{4 + 1 + (4)/(9) }


l = \sqrt{ (36 + 9 + 4)/(9) }


l = \sqrt{ (49)/(9) } = (7)/(9)

(I'm not sure of my answer tho)

Normally I'd see a plus sign between the x,y and z values of the r(t) equation, so im assuming these represent the x,y,z coordinates in terms of t.

So i calculated ∆r(t) and found the length of the equation using the formula for length

User Juha
by
5.6k points